Kinerja Inkubator Bayi dengan Pemanas Tanpa Listrik yang Dilengkapi Unit Pemantau Suhu dan Kelembaban Udara - Wihantoro W; Abdullah N Aziz; Mukhtar Effendi; Sukmaji A Raharjo (Department of Physics, Sebelas Maret University, 2016)
An infant incubator utilizing a non-electrical heater element and an add-on temperature and relative humidity controlling unit has been produced. Copper pipe in planar spiral construction which usually found as a radiator element in refrigerator was used as the heater element. Once the hot water filled into the element, it will served as heat energy source for (40 x 58 x 40) cm3volume of incubator’s baby compartment. Compartment’s performance (P) in providing the heat energy was to be found as 0.4 J/s and the average constant temperature achievable was 34.2 oC. Two of LM35 ICs were operated as dry and wet sensor each and served as the input for temperature and humidity quantities for baby’s compartment. These both sensors were set by CV-AVR package program which then was loaded into the ATMega8535 chip. An LCDscreen of 20x2 matrices was then used in displaying these both quantities. Dry and wet temperature sensors which were used to acquire the value of air temperature and relative humidity within baby’s compartment to be found have sensitivity value of 0.02 0.01 volt/oC and 0.03 0.01 volt/oC, each.